2017
DOI: 10.1111/apm.12729
|View full text |Cite
|
Sign up to set email alerts
|

Tim‐1+ B cells suppress T cell interferon‐gamma production and promote Foxp3 expression, but have impaired regulatory function in coronary artery disease

Abstract: Atherosclerosis and its associated coronary artery disease (CAD) represent another chronic low-grade inflammatory disorder. Regulatory B cells (Bregs) possess essential functions in maintaining peripheral tolerance and inhibiting pathogenic inflammation through IL-10. Here, we investigated one subset of Bregs, Tim-1 B cell, and its role in atherosclerosis and CAD patients. In healthy individuals, IL-10-producing B cells were predominantly found in the Tim-1 B cells. Upon stimulation of the B cell receptor (BCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…We demonstrated that CD19 + TIM-1 + could also participate in the IL-10 production in HIV + individuals, which has already been described in mice, where TIM-1 defects in B cells reduce the production of Breg IL-10 [40]. Moreover, it was demonstrated that IL-10-secreting B cells were concentrated in the TIM-1 + CD19 + B cells in healthy [41] and in HIV + individuals [19]. This IL-10 production by TIM-1 + B cells is related to their ability to inhibit IFN-γ production and to upregulate Foxp3 expression in T cells [41].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We demonstrated that CD19 + TIM-1 + could also participate in the IL-10 production in HIV + individuals, which has already been described in mice, where TIM-1 defects in B cells reduce the production of Breg IL-10 [40]. Moreover, it was demonstrated that IL-10-secreting B cells were concentrated in the TIM-1 + CD19 + B cells in healthy [41] and in HIV + individuals [19]. This IL-10 production by TIM-1 + B cells is related to their ability to inhibit IFN-γ production and to upregulate Foxp3 expression in T cells [41].…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, it was demonstrated that IL-10-secreting B cells were concentrated in the TIM-1 + CD19 + B cells in healthy [41] and in HIV + individuals [19]. This IL-10 production by TIM-1 + B cells is related to their ability to inhibit IFN-γ production and to upregulate Foxp3 expression in T cells [41]. TIM-1 + B cells were also determined to promote Foxp3 expression in CD4+ T cells in acute respiratory distress syndrome [42].…”
Section: Discussionmentioning
confidence: 99%
“…Tim-1 defects also increase proinflammatory cytokine production, including IL-1, IL-6, and TNF-α [20]. Further, Tim-1-deficient B cells enhance Th1 and Th17 cell responses and inhibit regulatory T cells [20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Several subsets of IL-10 producing B cells have been described in humans, their definition depending on the disease under study, the immunological context and the stimulation conditions. These include CD1d + CD5 + (43,44), Tim-1 + (15,16), immature transitional CD24 hi CD38 hi (11,41) and memory CD24 high CD27 + B cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, and due to the absence of subset-specific membrane markers or transcription factors, IL-10 secretion is still the hallmark feature used to distinguish Breg from the rest of the B cells (9,10). In humans, different B cell lineages that secrete this cytokine and have regulatory functions have been described, such as CD19 + CD24 high CD38 high (11), CD19 + CD24 high CD27 + (12), CD19 + CD5 + CD1d + (13,14), CD19 + Tim-1 + (15,16) and CD19 + CD25 + CD71 + CD73cells (7), depending on the stimulation conditions and the markers used to identify them. Nowadays, the majority of the studies in human samples pinpoint the CD19 + CD24 high CD38 high immature transitional B cell population as the most representative phenotypic signature of Breg cells (17).…”
Section: Introductionmentioning
confidence: 99%